Desain Prototype dan Implementasi Sistem Informasi Pencatatan Meter Air (SICAIR) - Maria, Evi; Edi, Sri Winarso Martyas; Widhiyaningrum, Sekar; Andana, Aji (Program Studi Sistem Informasi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) aims to improve access to and quality of drinking water and sanitation in rural areas. However, the manual management of water meter readings and billing by Kelompok Pengelola Sarana Prasarana Air Minum Sanitasi (KPSPAMS) Tirto Wening, Samirono Village, has led to issues with accuracy and timeliness of water bills. Therefore, this research aims to design a water meter recording system. The system design scope includes recording water meters, calculating bills, processing payments, and generating water usage reports. The development method employs a prototype approach with the Bootstrap framework. The resulting system, named SICAIR, provides accurate billing and water usage reports that meet user needs. SICAIR offers a solution to PAMSIMAS management issues related to the accuracy of meter readings and the timeliness of water bill generation in Samirono Village.